Elucidating the functions of gut microbiota from two edible dung beetle species: Implications for waste management and food industry - Syombua S. Mwanza; Cynthia M. Mudalungu; JohnMark Makwatta; James Kabii; Njogu M. Kimani; Chrysantus M. Tanga (PLoS ONE, 2025)
Dung beetle larvae are consumed globally, yet their gut microbiota across different geographical locations remains largely unexplored. This study examined the diversity and composition of the gut microbiota of two edible dung beetle species, Cetonia aurata and Rhinoceros beetle (Oryctes sp.), from three sites in Kenya. Using advanced molecular techniques, bacterial and fungal communities were sequenced. The most abundant bacterial phyla in C. aurata were Firmicutes (42.10%) and Bacteroidota (32.50%), while Oryctes sp. had higher levels of Proteobacteria (35.00%), Actinobacteriota (11.40%) and Desulfobacterota (7.40%). Fungal communities were dominated by Lecanoromycetes (92.60%) in Oryctes sp. and Saccharomycetes (92.60%) in C. aurata. Beta diversity analysis revealed that neither species phylogeny nor larval location significantly influenced the presence of specific microbes. Pathways related to nitrogen and carbon degradation were predicted in bacteria like Bacillus, Pseudomonas mosselii, and Proteiniphilum. This implies that bacteria and fungi from the gut of dung beetle larvae could be ideal targets for potential bio‐resource to eliminate waste pollution and opened an important window of opportunity for bio-based economy solutions. This work offers very practical solutions that have great business potential that can create a gigantic market ranging from functional foods to dietary supplements and therapeutic applications.